Creation of an engineered APC system to explore and optimize the presentation of immunodominant peptides of major allergens - Rosskopf, Sandra (Sci Rep, 2016)
We have generated engineered APC to present immunodominant peptides derived from the major aero-allergens of birch and mugwort pollen, Bet v 1(142–153) and Art v 1(25–36), respectively. Jurkat-based T cell reporter lines expressing the cognate allergen-specific T cell receptors were used to read out the presentation of allergenic peptides on the engineered APC. Different modalities of peptide loading and presentation on MHC class II molecules were compared. Upon exogenous loading with allergenic peptides, the engineered APC elicited a dose-dependent response in the reporter T cells and the presence of chemical loading enhancers strongly increased reporter activation. Invariant chain-based MHC class II targeting strategies of endogenously expressed peptides resulted in stronger activation of the reporters than exogenous loading. Moreover, we used Bet v 1 as model allergen to study the ability of K562 cells to present antigenic peptides derived from whole proteins either taken up or endogenously expressed as LAMP-1 fusion protein. In both cases the ability of these cells to process and present peptides derived from whole proteins critically depended on the expression of HLA-DM. We have identified strategies to achieve efficient presentation of allergenic peptides on engineered APC and demonstrate their use to stimulate T cells from allergic individuals.